Financial games for training - Kind, John (Routledge, Taylor & Francis Group, 2018)
"Accounting and finance have a reputation for complexity and dullness. Financial Games for Training aims to change these perceptions! It is an original collection of more than 65 brainteasers, crosswords, puzzles and quizzes plus all the solutions. They've been specially designed to bring a light-hearted but rigorous approach to the study and teaching of an otherwise 'boring' subject. Whether you're a student or executive, participant or tutor, here's the treasure chest you need to improve your grasp of finance for business. You won't think about the subject in quite the same way ever again!"--Provided by publisher